PENGARUH INFLUENCER MARKETING, DIGITAL MARKETING DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK ADES DI KOTA BATAM - joline (SCIENTIA JOURNAL, 2025)
This study aims to analyze the Influence Marketing, Digital Marketing and Promotion in Purchasing Decisions for Ades product in Batam City. In the ever-evolving digital era, it shows that Digital Marketing and Promotion have a positive and significant influence on Purchasing Decisions, while Influencer Marketing has an insignificant positive influence. These findings indicate the importance of the role of Influencer, Digital Marketing, and Promotions in improving customer Purchasing Decisions. The recommendation for companies is to focus more resources on collaboration with Influencers and Digital Marketing strategies to increase product attractiveness in the market. This research uses a quantitative method with a survey to respondents who are consumers of Ades product in Batam City.